THE CONCEPT OF VALUE IN RELIGIOUS PLURALITY IN INDONESIA (REFLECTION ON VERSES OF ÄªÅšÄ€ UPANIá¹¢AD) - Joyo, Puspo Renan; Maharani, Septiana Dwiputri (Institut Hindu Dharma Negeri Denpasar, 2021)
Indonesia is a pluralistic country. This plurality is indicated by the existence of ethnicities, races, customs, languages, and religions. Plurality does not only breed cooperation, but also conflict. The fact shows that religious plurality is one of the biggest challenges in Indonesia. This study aimed to explore the concept of value in the ÄªÅ›Ä Upaniá¹£ad verses which correlate with the plurality of religions in Indonesia. This research used a qualitative approach. Data collection in this study was carried out through document studies on primary and secondary data sources. The primary data sources in this study are ÄªÅ›Ä Upaniá¹£ad by Sri Aurobinda, The Principal Upanishads by S. Radhakrishnan, and The Upanisads: A Complete Guide by Cohen Signe, while secondary data sources include documents relevant to the object of the research material. The data analysis in this study used methodical steps of descriptive, interpretative, and holistic analysis, while the theory used is Gadamer's philosophical hermeneutic theory. The results of this study indicate that the verses in the ÄªÅ›Ä Upaniá¹£ad have a concept of value that is correlated with the plurality of religions in Indonesia: kinship, tolerance, and harmony; divinity, holiness, and glory; equality, justice, and non-discrimination; unity and oneness; brotherhood, empathy, love, and mutual respect.